Nuclear nightmares in the Philippines - Beaver, William (Journal of business ethics, 1994)
The construction of the Philippine's first nuclear power plant by Westinghouse has come to symbolize the corruption and cronyism of the Marcos' years. The plant has created so much controversy that it has yet to operate, in a country that desperately needs electrical power. The entire affair suggests that American multinationals cannot simply adopt the business practices of the host country, but instead must carefully analyze the political and business environments of their foreign based operations, and then take into account the long-term ethical implications of their decisions. The case also suggests that government needs to play a more active role in regulating multinationals, especially when sophisticated and potentially dangerous technologies are involved.